2011
DOI: 10.1007/s10503-011-9257-0
|View full text |Cite
|
Sign up to set email alerts
|

Solving a Murder Case by Asking Critical Questions: An Approach to Fact-Finding in Terms of Argumentation and Story Schemes

Abstract: In this paper, we look at reasoning with evidence and facts in criminal cases. We show how this reasoning may be analysed in a dialectical way by means of critical questions that point to typical sources of doubt. We discuss critical questions about the evidential arguments adduced, about the narrative accounts of the facts considered, and about the way in which the arguments and narratives are connected in an analysis. Our treatment shows how two different types of knowledge, represented as schemes, play a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…The ideas provided in this work have been a great influence on the hybrid theory (also indirectly via [33]). A major difference though is that the authors of [22] approach evidential and legal reasoning from a psychological, descriptive stance whilst we also claim to have more normative aims (in [9], for example, we propose a list of pitfalls one should avoid when drafting a rational and intelligible verdict in a case). Furthermore, [22] does not fully formally specify the connection between the evidence, the facts and the law.…”
Section: Discussion and Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideas provided in this work have been a great influence on the hybrid theory (also indirectly via [33]). A major difference though is that the authors of [22] approach evidential and legal reasoning from a psychological, descriptive stance whilst we also claim to have more normative aims (in [9], for example, we propose a list of pitfalls one should avoid when drafting a rational and intelligible verdict in a case). Furthermore, [22] does not fully formally specify the connection between the evidence, the facts and the law.…”
Section: Discussion and Related Researchmentioning
confidence: 99%
“…For instance, one reasonable story provides a counterargument to another. In our earlier work, we have suggested that arguments and stories are a kind of 'communicating vessels': a change in an argumentative analysis implies a change in an narrative analysis, and vice versa (cf., e.g., [9]). In the present setting of legal story schemes, there is the related issue how the legal conditions of a valid rule are connected to a legal story scheme.…”
mentioning
confidence: 99%
“…However, the basic hybrid theory does not tell us explicitly how we should reason in order to come to a good story. This implicit procedural character of the hybrid theory was made more clear in Bex and Verheij (2012), in which six critical questions based on the hybrid theory were proposed.…”
Section: The Hybrid Theory As a Methods For Legal Argumentationmentioning
confidence: 99%
“…Two of these, arguments and narratives, have been combined in the hybrid theory (Bex 2011, Bex and Verheij 2012. According to the hybrid theory, reasoning with evidence involves constructing narratives, or scenarios, about "what happened" in a case, which is arguably easiest from a cognitive point of view (Pennington andHastie 1993, Wagenaar et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation